2019
DOI: 10.1098/rsos.180941
|View full text |Cite
|
Sign up to set email alerts
|

The effect of uncertain bottom friction on estimates of tidal current power

Abstract: Uncertainty affects estimates of the power potential of tidal currents, resulting in large ranges in values reported for a given site, such as the Pentland Firth, UK. We examine the role of bottom friction, one of the most important sources of uncertainty. We do so by using perturbation methods to find the leading-order effect of bottom friction uncertainty in theoretical models by Garrett & Cummins (2005 Proc. R. Soc. A 461, 2563–2572. (doi:10.1098/rspa.2005.149410.1098/rspa.2005.1494); 2013 J. Fluid Mech. 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Garrett and Cummins (2005) have shown that there is a maximum amount of power that can be extracted from a tidal channel, and that both this maximum extractable power and the optimal turbine drag, λ 1 , depend solely on the value of λ 0 . A recent study by Kreitmair et al (2019) has used this simple channel model to show how uncertainty in the value of specific inputs (the bed roughness coefficient, in this case) can propagate through the model to produce uncertain optimal tunings and maximum power estimates. Uncertainty will be an important consideration for studies of real tidal power sites, where bed roughness and other parameters must be carefully calibrated prior to undertaking resource assessments, but is not considered in this study, where the aim is simply to compare between different idealised models of turbine performance.…”
Section: Tidal Channelmentioning
confidence: 99%
“…Garrett and Cummins (2005) have shown that there is a maximum amount of power that can be extracted from a tidal channel, and that both this maximum extractable power and the optimal turbine drag, λ 1 , depend solely on the value of λ 0 . A recent study by Kreitmair et al (2019) has used this simple channel model to show how uncertainty in the value of specific inputs (the bed roughness coefficient, in this case) can propagate through the model to produce uncertain optimal tunings and maximum power estimates. Uncertainty will be an important consideration for studies of real tidal power sites, where bed roughness and other parameters must be carefully calibrated prior to undertaking resource assessments, but is not considered in this study, where the aim is simply to compare between different idealised models of turbine performance.…”
Section: Tidal Channelmentioning
confidence: 99%
“…The effect of uncertainty in C d on these parameters is now explored. [9]. For all values of m C d , uncertainty in C d acts to increase the expected power slightly above the deterministic value.…”
Section: Resultsmentioning
confidence: 86%
“…The results shown on the right-hand axis of figure 5 are in good agreement with results shown in fig. 5 of Kreitmair et al [9], again dependent on choice of value for λ 0 .…”
Section: : 191127mentioning
confidence: 97%
See 2 more Smart Citations